Feasibility of the Olympic marathon under climatic and socioeconomic change - Takahiro Oyama; Jun’ya Takakura; Minoru Fujii; Kenichi Nakajima; Yasuaki Hijioka (Scientific Reports, 2022)
Abstract There are concerns about the impact of climate change on Olympic Games, especially endurance events, such as marathons. In recent competitions, many marathon runners dropped out of their races due to extreme heat, and it is expected that more areas will be unable to host the Games due to climate change. Here, we show the feasibility of the Olympic marathon considering the variations in climate factors, socioeconomic conditions, and adaptation measures. The number of current possible host cities will decline by up to 27% worldwide by the late twenty-first century. Dozens of emerging cities, especially in Asia, will not be capable of hosting the marathon under the highest emission scenario. Moving the marathon from August to October and holding the Games in multiple cities in the country are effective measures, and they should be considered if we are to maintain the regional diversity of the Games.